FREQUENCY OF PATIENT UNDERGOING GENERAL SURGERY HAVING HIGH BODY MASS INDEX-A GENDER BASED STUDY (The Research of Medical Science Review, 2025)
Introduction: Obesity is a significant risk factor influencing surgical outcomes, with gender-specific variations in prevalence. This study examines the frequency of patients undergoing general surgery with high body mass index (BMI) and its association with gender and hypertension at Gulab Devi Teaching Hospital, Lahore. Methodology: A cross-sectional study was conducted on 245 patients undergoing general surgery. BMI categories were determined, and associations with gender and hypertension were assessed using the chi-square test. Statistical significance was set at p < 0.05. Results: Among the patients, 68.2% were female and 31.8% were male. The mean BMI was 25.9 (14.9–53.8). A significant association was found between BMI and gender (χ² = 228.488, p = 0.005), with a higher proportion of females having an elevated BMI. Additionally, BMI showed a strong association with hypertension (χ² = 31.195, p < 0.000), indicating increased risk among obese individuals. Conclusion: High BMI is prevalent among surgical patients, with a higher proportion of affected females. The strong association between BMI and hypertension highlights the need for preoperative risk assessment. Preventive strategies should target obesity management to improve surgical outcomes.